O trabalho no setor de telecomunicações do Brasil: tendências gerais e empresa-espelho - Aquiles, Affonso Cardoso (2011)
This essay discusses the effects of the restructuring of the telecommunications sector in Brazil on the socio-occupational and labor relations in the sector. This started from the assumption that the changes do not end with the privatization of telecommunications in 1998, but remained with intensity in the first decade of this century, redefining the profile of workers and labor relations. Using the experience of a mirror company of telecommunications, the Global Village Telecom (GVT), the research seeks to understand how mutations of the telephone industry as a whole are manifested in the reality of a carrier created after privatization. The survey results point to a redefinition of the socio-occupational profile of workers in the telecommunications industry in the first decade of this century. Note the formation of a younger workforce with higher education and predominantly male. Moreover, it shows a process of precarious employment in the sector as a whole, especially with the drop in average earnings over the last decade. The analysis of GVT's experience, in turn, points to the existence of a format hybrid management of the labor force, in which classical elements coexist, taylorism-fordism, and flexible in organizational structure of the company. Note the marked instability of a framework of labor relations, especially with low wages, even though most employees are hired under a formal status indefinitely.